2019
DOI: 10.2174/1574891x13666180626170155
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-mycobacterial Activity of Three Medicinal Plants of Lamiaceae Family

Abstract: The studied medicinal plants showed notable effects against mycobacterial strains. Our results indicated that utilization of Lamiaceae family can be helpful for treatment of mycobacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…But this extract was not effective against M. abscessus [ 34 ]. An MDR-TB strain was inhibited by Z. multiflora extract at a concentration of 78 μg/mL showed by Kazemian et al However, 156 μg/mL was reported as a minimum inhibitory concentration of S. rechingeri and S. khuzestanica extracts against MDR-TB [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…But this extract was not effective against M. abscessus [ 34 ]. An MDR-TB strain was inhibited by Z. multiflora extract at a concentration of 78 μg/mL showed by Kazemian et al However, 156 μg/mL was reported as a minimum inhibitory concentration of S. rechingeri and S. khuzestanica extracts against MDR-TB [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…at 78 µg/mL while Satureja rechingeri and Satureja khuzestianica showed MICs of 156 µg/mL against MDR Mycobacterium tuberculosis. 127 Other EOs showing efficacy in studies against MDR-and XDR-TB are Myrtus communis L. 128 and Nigella damascena. 129 Our study showed LVO is a promising antimicrobial extract, which can be used in combinatory therapy and may possibly be effective in reviving the efficacy of carbapenem and other antibiotics against other resistant bacteria.…”
Section: Mdr and Xdr Tuberculosismentioning
confidence: 99%
“…at 78 µg/mL while Satureja rechingeri and Satureja khuzestianica showed MICs of 156 µg/mL against MDR Mycobacterium tuberculosis. 127 Other EOs showing efficacy in studies against MDR-and XDR-TB are Myrtus communis L. 128 and Nigella damascena. 129…”
Section: Mdr and Xdr Tuberculosismentioning
confidence: 99%
“…Among the studies performed on medical herbs, Lamiaceae (Labiatae) family are of pharmaceutical interest because of their potential antimicrobial properties. This family is distributed throughout the world and is consisted of more than 7000 species [6]. The geographical analysis showed that Satureja species (members of the Lamiaceae family) are found in mountainous areas in Iran, mainly in Western and Northern parts of the country [6].…”
Section: Introductionmentioning
confidence: 99%
“…This family is distributed throughout the world and is consisted of more than 7000 species [6]. The geographical analysis showed that Satureja species (members of the Lamiaceae family) are found in mountainous areas in Iran, mainly in Western and Northern parts of the country [6]. These species were formerly used as a traditional medicine to treat various diseases such as cramps, muscle pains, nausea, indigestion, diarrhea, and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%